Capital symbolique, consécration et marché des retraductions de littérature française en langue hongroise entre 2000 et 2020 - Adrienn Gulyás (Romanica Wratislaviensia)
This study discusses retranslations of French prose and drama into Hungarian between 2000 and 2020, in a Bourdieusian framework, using mixed methods, based on data provided by the National Library of Hungary. The results show that retranslations constitute 1.26% of the French corpus, i.e. 31 records out of 2452, with a very clear preference for retranslations of narrative works, mostly novels, that are no longer protected by copyright. Although they represent a highly limited and fragmented market, Hungarian retranslations of French literature increase the publishers’ and translators’ symbolic capital and have been on the rise since 2010.